Professor& Chief, Dept of General Medicine, Sree Balaji Medical College & Hospital, Chromepet, Chennai, Tamil Nadu - ANITHA S,; S. S. SUDHA, (International Journal of Pharma and Bio Sciences, 2018)
Several type synthetic dyes are available in market as colouring agent used in fabric, food and cosmetic industry. But bicolour or natural colour gains much importance due to its non-toxicity. These natural colours can be extracted from microbes. In this study, Streptomycetes sp has been employed as source of colouring agent. Pigment producing Streptomycetes sp has been isolated from the Soil samples collected from Nilgiri hills, Western Ghats, Tamilnadu, India. Streptomycetes was grown in modified Actinomycetes isolation medium and the pigment production was observed to be dark blue in colour. For better extraction of pigment, the Streptomyces cell mat was removed and the obtained broth was adjusted to acidic condition by using 0.1N Hydrochloric acid followed by centrifugation The extract was subjected to 2, 2 diphenyl-1-picrylhydrazyl (DPPH) antioxidant assay to determine the free radical scavenging activity and gas chromatography mass spectrometry (GC-MS) analysis to determine the presence of bioactive compounds. The pigment extract at the highest concentration 100 µg/ml exhibits free radical scavenging activity at the rate of 72% and GC-MS analysis reveals that the pigment possess 19 active compounds. The chromatography of mass spectrometry was matched with NIST and WILEY libraries to find out the following compounds such as Hexadecanyl di methylamine (C18H39N), Methanone (1-hydroxycyclohexyl) phenyl-Irgacure 184 (C13H16O2), 1,1,1,5,7,7,7-Heptamethyl-3-3bis(trimetylsiloxy) tetrasiloxane (C13H40O5Si6), and Hexadecanoic acid, methyl ester(C17H34O2) which are applied in cosmetics and fabric industries. The compounds such as 2-Pentanone,4-hydroxy-4-methyl-(CAS) (C6H12O2), 5,6-Dihydro -6-methyl-2H-pyran-2-one(C6H8O2), 5-methoxy-3-pentene-2-ol (C6H8O2) and 3A-Hydroxy-1,2,3,3A.8,8A Hexahydropyrrol (2,3B) Indde (C11H14N2O) are used as antimicrobial compounds. It is concluded that, the pigment produced by Streptomycetes sp can be processed further to apply as colouring agent in fabric and in cosmetic industries.